Community-based Environmental Management: The Case of St. Martin’s Island, Bangladesh - Sharmistha Basak; Anil Kumar Chaudhary (Journal of International Agricultural and Extension Education, 2025)
Policies and actions taken to conserve local natural resources should focus on the needs and interests of multiple stakeholders who are involved in a selected context. However, sometimes, local contextual factors and barriers are not prioritized in natural resource conservation efforts. As a result, the primary goal of environmental policies, which is to conserve natural resources, becomes unattainable, and the policies fail to leave long-term and sustainable impacts on local communities. This study examines the factors influencing the environmental decision-making among various stakeholders to mitigate the environmental degradation of St. Martin’s Island, Bangladesh. The two primary objectives of this study were to explore the contextual factors that inform local environmental management efforts on St. Martin’s Island and analyze the barriers that stakeholders face while supporting conservation efforts on the island. This ethnographic qualitative study used semi-structured interviews and participant observation. The study identified a number of crucial contextual factors and barriers that prevented locals’ active participation in environmental decision-making. The findings revealed that economic reliance on local natural resources, extensive tourism activities, limited opportunities for collaborative actions at multiple levels, and inadequate local facilities contribute significantly to the overall scenario of environmental degradation on St. Martin’s Island. These findings can guide Extension efforts focusing on environmental degradation in international contexts. The findings also have the potential for future research focusing on stakeholder engagement in environmental decision-making.
Keywords: Public participation; environmental management; environmental governance; contextual factors and barriers to stakeholder engagement